Magnetostratigraphy of a greigite‐bearing core from the South Yellow Sea: Implications for remagnetization and sedimentation. Issue 10 (25th October 2014) - Liu, Jianxing; Shi, Xuefa; Liu, Qingsong; Ge, Shulan; Liu, Yanguang; Yao, Zhengquan; Zhao, Quanhong; Jin, Chunsheng; Jiang, Zhaoxia; Liu, Shengfa; Qiao, Shuqing; Li, Xiaoyan; et al.
Abstract Sediments from the continental shelf are sensitive to sea level, climatic changes, and local tectonic history. In this study, we carried out a high‐resolution magnetostratigraphic investigation on the longest core (NHH01, 125.64 m) recovered from the South Yellow Sea (SYS). An abnormal interval dominated by negative inclinations was discovered by applying alternating field demagnetization (AFD) on samples from a greigite‐bearing layer (44.90–51.80 m). In contrast, the inclinations of most greigite‐bearing samples changed from negative to positive when heated to 360°C. This strongly indicates that this inclination anomaly revealed by the AFD alone is not a true negative subchron. After neglecting the effects of greigite‐bearing layers, the straightforward correlation of the interpreted magnetostratigraphy defines the Matuyama‐Brunhes boundary (781 ka) and the Jaramillo top (990 ka) at 68.64 m and 101.54 m, respectively. The linearly extrapolated basal age of the core is 1.10 Ma. In addition, several short‐lived inclination anomalies can be tentatively assigned to magnetic excursions, which indicates that the sedimentation could be continuous even at the millennial time scale at depth intervals bracketing these fast geomagnetic events. Moreover, the excellent correspondence between clay content variations of the core and the marine oxygen isotope record indicates the potential of clay content as a paleoclimatic proxy in the studied region in the past 1 Ma. In brief, our study provides not only a robust age model in the SYS but also a methodological guide for paleomagnetic studies in continental shelf region.